Thematic Analysis: : The ‘Good’, the ‘Bad’ and the ‘Ugly’ - Finlay, Linda (European Journal for Qualitative Research in Psychotherapy, 2021)
Thematic analyses can take multiple forms, some of them systematic, others intuitive. In practice, published research that involves thematic analysis comes is all sorts of shapes and styles: some good, some bad, and some just plain ugly. In this article, I attempt to clarify the nature and practice of thematic analysis. I offer concrete examples of what I consider to be good practice, highlighting instances where I think the thematic analysis has been conducted in an appropriately rigorous way, yielding rich, informative findings. First, different types of thematic analyses are identified and contrasted. The second section considers the stages and process of conducting an analysis. The third section explores four key criteria to evaluate thematic analysis: Rigour, Resonance, Reflexivity and Relevance – the 4 R’s. Throughout, I emphasise that there is no one way to do thematic analysis. The form of analysis engaged depends on the research and methodological context as well as on the type of data collected, the researcher’s own preferences, and what is required by others (e.g., the journal, examiners).